PENGARUH LAYANAN INFORMASI DALAM UPAYA MENINGKATKAN PEMAHAMAN TENTANG HIV/AIDS BAGI SISWA SMA SRIGUNA PALEMBANG - Aris, Aris Siswanto (KOPASTA : Jurnal Program Studi Bimbingan Konseling, 2019)
The United Nations Programme on HIV/AIDS (UNAIDS) reports the number of people living with HIV in 2012 as much as 35.3 million people. In the same year AIDS mortality rate amounted to 1.6 million people and as many as 2.3 million people have HIV. Seeing the high number of people with HIV/AIDS, it is the government's duty to continue socializing about HIV/AIDS. At school, tutoring and counseling teachers provide an important role to provide information about the disease, especially high school students. At this time a group of teenagers in susceptible to age 10-19 years is a period of rapid growth and development both physical, psychological and intellectual. Based on the results of the research in the field, many students do not understand about HIV/AIDS. One way of addressing the problem is to provide information services. The purpose of this research is to find out if there is an influence on information services in an effort to improve understanding of HIV/AIDS for students. This research uses quantitative methods with quasi experimental design. The subject of this research is high school student Sriguna Palembang XI IPA 2. The research Instrument uses a Likert scale model, subsequently analysed using Test-T. In general, this research shows the influence of information services in the effort to improve understanding of HIV/AIDS. Based on the results of the research that has been obtained, the cooperation of various parties is expected to improve students ' understanding.Keywords: Information Services, HIV/AIDS